2009
DOI: 10.1002/ange.200805511
|View full text |Cite
|
Sign up to set email alerts
|

[Co@Ge10]3−: An Intermetalloid Cluster with Archimedean Pentagonal Prismatic Structure

Abstract: Anorganisches Pentaprisman: Die ungewöhnliche Struktur des Anions [Co@Ge10]3−, das aus K4Ge9 und [Co(C8H12)(C8H13)] in Ethylendiamin entstand, lässt Fragen nach der Art der Bindung aufkommen. Der quasi‐D5h‐symmetrische Zintl‐Cluster ist ein einzigartiges Beispiel für einen nichtdeltaederförmigen ligandenfreien Cluster. Die delokalisierten Bindungen des Anions werden im Bild durch eines der bindenden Orbitale dargestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
9

Year Published

2009
2009
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 94 publications
(45 reference statements)
3
56
0
9
Order By: Relevance
“…In both the lead 10 and 12 series, the PE data for the filled and empty clusters are similar in regard to both their electron binding energies and their complexities, suggesting that their electronic structures are primarily lead based. (69,70). Table 1 shows the optimized geometries (NRLMOL) for the four most viable structures for the PtPb 10 n− ions where n ¼ 0, 1, 2, 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both the lead 10 and 12 series, the PE data for the filled and empty clusters are similar in regard to both their electron binding energies and their complexities, suggesting that their electronic structures are primarily lead based. (69,70). Table 1 shows the optimized geometries (NRLMOL) for the four most viable structures for the PtPb 10 n− ions where n ¼ 0, 1, 2, 3.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the Sn 9 4− and Cu@Sn 9 3− ions are both formally nido 2n þ 4 clusters (i.e., the same structural class) but have C 4v and D 3h structures, respectively. The persistence of this D 4d struc- ture for the Pb 10 1−∕2− clusters in the condensed state is somewhat surprising in view of the highly dynamic nature of the M@Pb 10 2− structures in solution (i.e., there are two or more structures very close in energy) and the existence of alternate structures in the closely related germanides (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…• [13]. The cod ligand in 2 is coordinated with a similar boat conformation as the one in 3a, whereas the C 8 H 13 ligand adopts a tub-like form with η 3 -cyclooctenyl coordination (see Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The anion [Co@Ge 10 ] 3− (figure 7d) with an unprecedented structure emerged during the reaction of K 4 Ge 9 with Co(C 8 H 12 )(C 8 H 13 ) (Wang et al 2009 bicapped square anti-prism would have been forecast for the shape of this species, and DFT calculations performed for [Co@Ge 10 ] 3− revealed that the potential surface for this cluster is rather flat, with an energy difference of 13.3 kcal mol −1 between the stationary points. Therefore, it can easily transform between the favoured D 5h -symmetric and the energetically unpropitious D 4d -symmetric arrangement (Wang et al 2009). The same calculations for [Ni@Ge 10 ] 2− revealed an energetic minimum for the D 4d geometry, while the pentagonal prism corresponds to a ground state of 5.33 kcal mol −1 (King et al 2008;Wang et al 2009).…”
Section: (D) Endohedrally Filled Clusters: Intermetalloidsmentioning
confidence: 99%
“…Therefore, it can easily transform between the favoured D 5h -symmetric and the energetically unpropitious D 4d -symmetric arrangement (Wang et al 2009). The same calculations for [Ni@Ge 10 ] 2− revealed an energetic minimum for the D 4d geometry, while the pentagonal prism corresponds to a ground state of 5.33 kcal mol −1 (King et al 2008;Wang et al 2009). Thus for these clusters the global minimum cannot be determined indisputably, whereas the empty [Ge 10 ] 2− unit preferentially adopts a bicapped square anti-prism (King et al 2006 (Zhou et al 2009b).…”
Section: (D) Endohedrally Filled Clusters: Intermetalloidsmentioning
confidence: 99%